(untitled) (Journal of Health Sciences, 2024)
Introduction: Gastric cancer (GC), as a multifactorial disease, exhibits a complex pathogenesis, having intra and inter-tumor heterogeneity, challenging the efficacy of current treatments. GC is a major global health problem, and better diagnostic and therapeutic strategies are needed, leading to further biomarkers research associated with innovative targeted therapies. Our aim was to study human epidermal growth factor receptor 2 (HER2), Epstein Barr virus (EBV), and CD34 expression in GC samples to understand the relationship between these markers and relate them with the clinicopathological characteristics. Methods: Thirty samples of primary carcinoma gastrectomy cases performed between February 2017 and December 2021 at the Hospital Distrital da Figueira da Foz, EPE, were studied after approval by the Ethics Committee. Immunohistochemistry assays were performed in sections of the selected tumor representative samples. Results: All samples were negative for EBV and only two GC samples were positive for HER2. A significant statistical relationship was found between gender and CD34+ stroma cells. Microvascular density and stroma CD34+ cells presented relations with clinicopathological features and a positive tendency between them. Our study was able to identify a relationship between CD34+ stroma cells and females. Conclusion: With this study, we mainly explored the potential role of CD34 as a biomarker in GC and projected possible associations of prognostic and therapeutic value toward other HER2 and EBV markers.